Cinta Compressiva Na Função Ventilatória Em Pacientes Submetidas À Abdominoplastia - Kosloski, Fabiane Regina [UNIFESP] (2018)
Introduction: Abdominoplasty is one of the most frequent plastic surgeries. According to data from the Brazilian Society of Plastic Surgery, this is the third most frequent plastic surgery in Brazil and, according to the American Society of Plastic Surgery, is the fifth most performed in the United States. It is indicated for the correction of aesthetic changes of the abdominal wall, aiming at the correction of muscle - aponeurotic sagging and resection of excess skin and fat. The purpose of this study was to evaluate the effect of compressive garment on ventilatory function in patients undergoing abdominoplasty. Methods: Thirtyfour female patients were selected from the Abdominal Wall Sector of the Plastic Surgery Outpatient Clinic of UNIFESP-SP. They were randomly divided into two groups of patients: the control group, who underwent abdominoplasty with the use of compressive garment in the postoperative period, Macom brand, high waist, with closure in the anterior part, being used for the period consecutive days in the postoperative period. Respiratory evaluation was performed in the preoperative period, first, seventh and fourteenth postoperative day. In the intervention group, respiratory evaluation was also performed in the same periods, but without the use of compressive garment. All patients received the Informed Consent Term for reading, clarification of the research and signed. Results: There was a statistically significant decrease for Maximum Inspiratory Pressure (maxIP), Maximum Expiratory Pressure (maxEP), Forced Vital Capacity (FVC), Forced Expired Volume (FEV), Expiratory Flow Peak (EFP), Forced Expiratory Flow (FEF), Forced Vital Capacity (FVC), Slow Vital Capacity (SVC) and inspiratory capacity (IC) in the control and no-strap groups for all the evaluated periods. However, when comparing controls or without strap in each of the periods, we found significant improvement for the control groups only for maxPE, FVC, FEV1, SVC and IC. Conclusion: The use of compressive 70 bandage worsens the ventilatory function after abdominoplasty.